Differential Equation Questions

Question Number 105603 by bemath last updated on 30/Jul/20

$$\frac{{d}^{\mathrm{2}} {y}}{{dx}^{\mathrm{2}} }−\mathrm{4}\frac{{dy}}{{dx}}+{y}\:=\:{a}\:\mathrm{sin}\:\mathrm{2}{x} \\$$

Answered by bobhans last updated on 30/Jul/20

$$\mathcal{H}{omogenous}\:{equation} \\$$$$\nu^{\mathrm{2}} −\mathrm{4}\nu+\mathrm{1}=\mathrm{0}\:\rightarrow\nu=\frac{\mathrm{4}\pm\mathrm{2}\sqrt{\mathrm{3}}}{\mathrm{2}} \\$$$$\nu=\mathrm{2}\pm\sqrt{\mathrm{3}}\:\Rightarrow{y}_{{h}} =\:{C}_{\mathrm{1}} {e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right){x}} +{C}_{\mathrm{2}} {e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right){x}} \\$$$${Let}\:{particular}\:{solution}\: \\$$$${y}_{{p}} =\:{A}\mathrm{sin}\:\mathrm{2}{x}+{B}\mathrm{cos}\:\mathrm{2}{x} \\$$$${y}_{{p}} '=\mathrm{2}{A}\mathrm{cos}\:\mathrm{2}{x}−\mathrm{2}{B}\mathrm{sin}\:\mathrm{2}{x} \\$$$${y}_{{p}} ''=−\mathrm{4}{A}\mathrm{sin}\:\mathrm{2}{x}−\mathrm{4}{B}\mathrm{cos}\:\mathrm{2}{x} \\$$$${comparing}\:{coefficient}\:{LHS}\:{and}\:{RHS} \\$$$$\begin{cases}{\mathrm{8}{B}−\mathrm{3}{A}={a}}\\{\mathrm{8}{A}=\mathrm{3}{B}}\end{cases} \\$$$$\begin{cases}{{A}=\frac{\mathrm{3}{a}}{\mathrm{55}}\:\&\:{B}=\frac{\mathrm{24}{a}}{\mathrm{165}}}\\{{y}_{{p}} =\:\frac{\mathrm{3}{a}}{\mathrm{55}}\mathrm{sin}\:\mathrm{2}{x}+\:\frac{\mathrm{24}{a}}{\mathrm{165}}\mathrm{cos}\:\mathrm{2}{x}}\end{cases} \\$$$${complete}\:{solution} \\$$$${y}\:=\:{C}_{\mathrm{1}} {e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right){x}} +{C}_{\mathrm{2}} {e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right){x}} +\frac{\mathrm{3}{a}}{\mathrm{55}}\mathrm{sin}\:\mathrm{2}{x}+\frac{\mathrm{24}{a}}{\mathrm{165}}\mathrm{cos}\:\mathrm{2}{x} \\$$$$\bigstar \\$$$$\\$$

Answered by mathmax by abdo last updated on 01/Aug/20

$$\mathrm{y}^{''} −\mathrm{4y}^{'} \:+\mathrm{y}\:=\mathrm{asin}\left(\mathrm{2x}\right) \\$$$$\mathrm{h}\rightarrow\mathrm{r}^{\mathrm{2}} −\mathrm{4r}\:+\mathrm{1}\:=\mathrm{0}\:\rightarrow\Delta'\:=\mathrm{4}−\mathrm{1}\:=\mathrm{3}\:\Rightarrow\mathrm{r}_{\mathrm{1}} =\mathrm{2}+\sqrt{\mathrm{3}}\mathrm{and}\:\mathrm{r}_{\mathrm{2}} =\mathrm{2}−\sqrt{\mathrm{3}} \\$$$$\Rightarrow\mathrm{y}_{\mathrm{h}} \:=\alpha\:\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \:+\beta\:\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} \:=\alpha\mathrm{u}_{\mathrm{1}} \:+\beta\:\mathrm{u}_{\mathrm{2}} \\$$$$\mathrm{W}\left(\mathrm{u}_{\mathrm{1}} \:,\mathrm{u}_{\mathrm{2}} \right)\:=\begin{vmatrix}{\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \:\:\:\:\:\:\:\:\:\:\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} }\\{\left(\mathrm{2}+\sqrt{\mathrm{3}}\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \:\:\:\:\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} \right.}\end{vmatrix} \\$$$$=\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{e}^{\mathrm{4x}} −\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{e}^{\mathrm{4x}} \:=−\mathrm{2}\sqrt{\mathrm{3}}\mathrm{e}^{\mathrm{4x}} \:\neq\mathrm{0} \\$$$$\mathrm{W}_{\mathrm{1}} =\begin{vmatrix}{\mathrm{o}\:\:\:\:\:\:\:\:\:\:\:\:\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} }\\{\mathrm{asin}\left(\mathrm{2x}\right)\:\:\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} }\end{vmatrix}=−\mathrm{a}\:\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right) \\$$$$\mathrm{W}_{\mathrm{2}} =\begin{vmatrix}{\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \:\:\:\:\:\:\:\:\:\:\:\:\mathrm{0}}\\{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \:\:\:\:\mathrm{asin}\left(\mathrm{2x}\right)}\end{vmatrix}=\mathrm{a}\:\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right) \\$$$$\mathrm{v}_{\mathrm{1}} =\int\:\frac{\mathrm{w}_{\mathrm{1}} }{\mathrm{w}}\mathrm{dx}\:=−\int\:\:\frac{\mathrm{a}\:\mathrm{e}^{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right)}{−\mathrm{2}\sqrt{\mathrm{3}}\mathrm{e}^{\mathrm{4x}} }\mathrm{dx} \\$$$$=\frac{\mathrm{a}}{\mathrm{2}\sqrt{\mathrm{3}}}\int\:\:\mathrm{e}^{\left(−\mathrm{2}−\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right)\mathrm{dx}\:=\frac{\mathrm{a}}{\mathrm{2}\sqrt{\mathrm{3}}}\:\mathrm{Im}\left(\int\:\mathrm{e}^{−\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}+\mathrm{2ix}} \mathrm{dx}\right)\:\mathrm{but} \\$$$$\int\:\:\mathrm{e}^{−\left(\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \mathrm{dx}\:=−\frac{\mathrm{1}}{\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}}\:\mathrm{e}^{−\left(\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \\$$$$=−\frac{\mathrm{2}+\sqrt{\mathrm{3}}−\mathrm{2i}}{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)^{\mathrm{2}} +\mathrm{4}}\:\mathrm{e}^{−\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \left\{\mathrm{cos}\left(\mathrm{2x}\right)+\mathrm{isin}\left(\mathrm{2x}\right)\right\}\:=... \\$$$$\mathrm{v}_{\mathrm{2}} \:=\int\:\frac{\mathrm{w}_{\mathrm{2}} }{\mathrm{w}}\mathrm{dx}\:=\int\:\frac{\mathrm{a}\:\mathrm{e}^{\left(\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right)}{−\mathrm{2}\sqrt{\mathrm{3}}\mathrm{e}^{\mathrm{4x}} }\mathrm{dx}\:=−\frac{\mathrm{a}}{\mathrm{2}\sqrt{\mathrm{3}}}\int\:\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \mathrm{sin}\left(\mathrm{2x}\right)\mathrm{dx} \\$$$$=−\frac{\mathrm{a}}{\mathrm{2}\sqrt{\mathrm{3}}}\:\mathrm{Im}\left(\int\:\:\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \mathrm{dx}\right)\:\mathrm{and} \\$$$$\int\:\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \mathrm{dx}\:=\frac{\mathrm{1}}{−\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}}\:\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \\$$$$=−\frac{\mathrm{1}}{\mathrm{2}−\sqrt{\mathrm{3}}−\mathrm{2i}}\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}+\mathrm{2i}\right)\mathrm{x}} \:=−\frac{\mathrm{2}−\sqrt{\mathrm{3}}+\mathrm{2i}}{\left(\mathrm{2}−\sqrt{\mathrm{3}}\right)^{\mathrm{2}} \:+\mathrm{4}}\mathrm{e}^{\left(−\mathrm{2}+\sqrt{\mathrm{3}}\right)\mathrm{x}} \left\{\mathrm{cos}\left(\mathrm{2x}\right)+\mathrm{isin}\left(\mathrm{2x}\right)\right\} \\$$$$\mathrm{rest}\:\mathrm{to}\:\mathrm{finish}\:\mathrm{tbe}\:\mathrm{calculus}... \\$$$$\Rightarrow\mathrm{y}_{\mathrm{p}} =\mathrm{u}_{\mathrm{1}} \mathrm{v}_{\mathrm{1}} \:+\mathrm{u}_{\mathrm{2}} \mathrm{v}_{\mathrm{2}} \:\Rightarrow\mathrm{the}\:\mathrm{general}\:\mathrm{solution}\:\mathrm{is} \\$$$$\mathrm{y}\:=\mathrm{y}_{\mathrm{h}} \:+\mathrm{y}_{\mathrm{p}} \\$$